Effect of damage and support damping mechanisms on unimorph piezoelectric energy harvester. (September 2019) - Khazaee, Majid; Rezania, Alireza; Rosendahl, Lasse
Damping plays a critical role in power generation by piezoelectric energy harvesting, and yet there is a lack of sensitivity studies on different sources of damping. In this paper, two damping sources in unimorph piezoelectric energy harvesters, namely support loss and damage damping mechanisms, are experimentally investigated. Variations of the power generation are evaluated with respect to the sources of damping. Accordingly, the power generation model is developed according to the experimental results in this work and using a single degree of freedom analytical model. This study focuses on the debonding effect, as an internal damping source, and support loss, as a critical source of external energy dissipation. The results show that the debonding reduces the output power dramatically at resonance and, particularly, at anti-resonance frequencies. Moreover, investigation of the support loss shows that the material of clamp as well as installation torque have an impact on the support loss and, consequently, affect the output power.